(untitled) (Transport systems and technologies, 2018)
The article presents the results of research on the strength of an improved structural design of a wagon-platform of an articulated type during transport on a railway ferry. In order to ensure the reliability of the fixing of the wagon-platform in relation to the par-rail of the railway ferry, it is proposed to install on its bearing structure knots for fastening of chain ties. In order to determine the dynamic loads that act on the carrier construction of the platform wagon, a mathematical model of the carriage movements during the main types of fluctuations of the railway ferry has been created. It is taken into account that the wagon platform is rigidly fixed relative to the deck and moves along with it. The accelerations received as components of the dynamic load acting on the bearing structure of the platform car are taken into account in the study of its durability. It was established that the maximum equivalent stresses in the bearing construction of the carriage-platform do not exceed the permissible ones. The carried out researches will promote increase of efficiency of functioning of combined transfers in the direction of international transport corridors.